2021
DOI: 10.1002/ange.202104591
|View full text |Cite
|
Sign up to set email alerts
|

Deracemization of Carbohelicenes by a Chiral Perylene Bisimide Cyclophane Template Catalyst

Abstract: Deracemization describes the conversion of a racemic mixture of a chiral molecule into an enantioenriched mixture or an enantiopure compound without structural modifications. Herein, we report an inherently chiral perylene bisimide (PBI) cyclophane whose chiral pocket is capable of transforming a racemic mixture of [5]-helicene into an enantioenriched mixture with an enantiomeric excess of 66 %. UV/Vis and fluorescence titration studies reveal this cyclophane host composed of two helically twisted PBI dyes has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…14c). The vibronic fine structure of the S 0 → S 1 absorption band at ~600 nm is less pronounced than for other bay substituted perylene bisimide cyclophanes 22,35,47 and the absorbance of the S 0 → S 2 band is rather strong which could be rationalized by a significant involvement of the phenyl subsitutents in this transition as supported by TD-DFT calculations (Supplementary Fig. 18).…”
Section: Structural and (Chiro-)optical Propertiesmentioning
confidence: 67%
See 2 more Smart Citations
“…14c). The vibronic fine structure of the S 0 → S 1 absorption band at ~600 nm is less pronounced than for other bay substituted perylene bisimide cyclophanes 22,35,47 and the absorbance of the S 0 → S 2 band is rather strong which could be rationalized by a significant involvement of the phenyl subsitutents in this transition as supported by TD-DFT calculations (Supplementary Fig. 18).…”
Section: Structural and (Chiro-)optical Propertiesmentioning
confidence: 67%
“…In the case of helicene structures, homochiral self-recognition is accepted to be a general trend in noncovalent bonding events 20,21 . In this context, the homochiral supramolecular complexes observed upon encapsulation of [4]-and [5]-carbohelicenes within an inherently chiral PBI cyclophane introduced recently by us extends this empirical result to non-identical molecules with structural analogies by revealing the perfect accommodation of substrates with the same configuration as the adjacent PBIs within a tailored cavity 22 .…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…[11] Whilst our initial cyclophane designs based on perylene bisimide (PBI) units did not afford the desired open cavities for guest encapsulation due to the strong intermolecular interactions between the larger π-planes of these dyes, [12] in 2015 we finally accomplished the synthesis of the first PBI cyclophane acting as a host for various PAHs. [13] Still, however, due to the restricted length of the PBI moiety the cavity of this and other meanwhile reported PBI cyclophanes [14] remains rather small, enabling only binding of a limited number of guests such as perylene with high affinity as required for photophysical studies on such hostguest complexes in dilute solution. To overcome this deficiency, here we introduce a new cyclophane comprising of larger terrylene bisimide (TBI) moieties.…”
mentioning
confidence: 90%
“…In the recent decade, molecular aggregates with supramolecular chirality 1 have gained considerable attention and been investigated widely due to their assembly mechanism 2 and applications, such as in chiral recognition and sensing, 3 supramolecular chiral catalysis, 4 chiral optic and electronic devices, 5 and biomaterials. 6 It has been demonstrated that for π-conjugated molecules, such as porphyrins, 7 oligo( p-phenylene vinylene)s, 8 perylene and naphthalene bisimides, 9 hexabenzocoronenes, 10 etc., supramolecular chirality and structural helicity can be obtained for one-dimensional π-stacks by introducing side chains with a permanent chiral center.…”
Section: Introductionmentioning
confidence: 99%